Are state mindfulness and state work engagement related during the workday?. Issue 1 (2nd January 2018) - Tuckey, Michelle R.; Sonnentag, Sabine; Bryan, Janet
ABSTRACT: Given the growing interest in mindfulness in the workplace and the established importance of work engagement for work-related health and well-being, we explore the relationships between these 2 positive psychological states as they vary naturalistically over the workday. Utilising data from 3 measurement occasions per day (before work, mid-workday, and end-workday), we track natural variations in state mindfulness and state work engagement to create a fine-grained picture about their reciprocal relationships within the workday. A sample of 94 university employees completed multiple diary entries per day, for 10 working days. Data were analysed using multilevel structural equation modelling in MPlus, testing within-person pathways between mindfulness and work engagement across the day. Although state work engagement was a predictor of subsequent state mindfulness, state mindfulness did not predict subsequent state work engagement when controlling for earlier within-day work engagement. Overall, the within-day associations between mindfulness and work engagement were weak. We note the high within-day stabilities of state mindfulness and state work engagement, and discuss whether job and personal resources as well as task features might be moderators in the relationships between these constructs.